Transmissão de imagens e vídeo utilizando o padrão IEEE 802.15.4 / ZIGBEE - Müller, Virgílio Fries [UNESP] (2015)
The demand for wireless network communications solutions technology wireless are integrated into the everyday and each day more embedded and valued in our midst. In this work the study of the feasibility of using wireless networkWPAN (IEEE 802.15.4) for video transmission with the Zigbee standard was done. For improve the capability of transmission of images and video compression techniques were used. For accomplish of this work the following tools are used: JAVA and C programming languages, aTube Catcher free software for video compression, connection modules, Atmel boards and transceiver. Tests were performed with images and MPEG-4 video and the results showed the feasibility of transmission. Besides, measurements with file compression with images and video, packet loss ratio with distance and data transmission latency were made